Masonika i antymasonika w prywatnym księgozbiorze Witolda Kazimierza Czartoryskiego - Seroka, Katarzyna (Saeculum Christianum. Pismo Historyczne, 2023)
Prince Witold Kazimierz Czartoryski was born on March 10, 1876 in Paris. He was the son of Władysław Czartoryski (1828–1894) and his second wife, the French princess Margaret of Orleans (1846–1893). In France, Witold Kazimierz gathered a collection of over 25,000 books of exceptional intellectual value and various topics. His book collection had a universal, humanistic character. Although Prince Czartoryski was a deeply religious person (in his collection, books on religious studies held a special place), he also collected an interesting group of 836 publications on topics related to freemasonry, occultism and broadly understood metaphysics. The article presents and discusses a group of masonic and anti-masonic publications from the collection of Witold Kazimierz Czartoryski’s library, currently located in the Library of the University of Lviv.